Ordine pubblico e azione giurisdizionale. Il modello di ordine pubblico proposto in sede giurisdizionale anche a proposito delle modalità di esercizio della libertà religiosa (Stato, Chiese e pluralismo confessionale, 2016)
SOMMARIO: 1. Premessa - 2. L’evoluzione storica di fonte costituzionale del concetto di ordine pubblico - 3. Il modello di ordine pubblico internazionale ed europeo - 4. … e nel diritto internazionale privato - 5. Composizione e settore di applicazione dell’ordine pubblico in relazione con l’ordinamento giuridico italiano - 6. L’ordine pubblico nel procedimento di delibazione - 7. L’ordine pubblico e il limite alle modalità di espressione della libertà religiosa.Public Order and Legal Action. The Public Order model proposed at the jurisdictional level, including the ways in which religious freedom is exercise ABSTRACT: In the Italian multicultural system in which religious practices are finding new channels of existence and expression the concept of public order represents the extreme limit within which the judicial system must continually and autonomously promote the carrying out of adjustments to the existing normative structure, values and constitutional principles, in order to guarantee the rights they attribute to individuals in its territory.A process of continuous, well-pondered monitoring of the very concept of public order –including the relevance that that value holds beyond the country’s national borders –permits the judicial system to place the right to religous freedom and its manifestations within their rightful context; in this logic the elements of ‘space’ and ‘time’ acquire an important role in an updated version of the right to religious freedom, i.e. individuals’ability to worship without any reference to State-determined religious institutions, or –inversely - to freely profess their atheist convictions
Keywords: Matrimonio